Convas: Guidelines for Gamifying Learning Management Systems - HAGE, JOHAN; WILLMAN, OSKAR (My University, 2019)
Gamification is an increasingly popular topic, being implemented in a wide variety of sectors with the intent to increase user engagement and motivation. One sector in which gamification shows great promise is the sector of education and learning, as the motivational effects of gamification can be of great use when engaging students in various educations. While the need for educated people is ever increasing, student attendance has been shown to be on the recline [10]. This thesis aims to explore the use of gamification in higher education to increase student motivation and engagement in order to tackle this problem. The topic of gamification in higher education was explored through the design and implementation of a gamified experience in a Learning Management System targeted at students in higher education. The gamified experience was constructed with the help of GWEN, a gamification service developed by Insert Coin. Through thorough user testing and an iterative design process, insights gained from the design was used to produce a set of guidelines which depicts recommended gamification elements to incorporate in a digital learning platform in order to create an experience which makes for an as positive impact on students motivation and engagement as possible. The project resulted in both a prototype of a learning management system called Convas, which incorporates various gamification elements, as well as a set of guidelines aimed to help future designers with designing similar systems.
Keywords: Gamification; Learning; Education; Motivation; Learning Management System